Animal Nullius: Review of Irus Braverman, Settling Nature: The Conservation Regime in Palestine-Israel (UMN, 2023) - Boast, Hannah (Humanimalia, 2023)
Review of: Irus Braverman. Settling Nature: The Conservation Regime in Palestine-Israel. Minneapolis: University of Minnesota Press, 2023. 362 pp. 47 b&w photos. 116.00 (hb) ISBN 978-1-5179-1205-5 29.00 (pb) ISBN 978-1-5179-1526-1